LIXO ELETRÔNICO E A CONTRIBUIÇÃO DA POPULAÇÃO COM O MEIO AMBIENTE EM PRESIDENTE PRUDENTE - Nádia de Souza Bastos; Leila Maria Sotocorno e Silva; Rebeca Delatore S. Guerino (Colloquium Exactarum, 2011)
This study aimed to evaluate the level of environmental consciousness of the population of Presidente Prudente in relation to the discard of electronics residues. It was applied a questionnaire to 73 people who participated in the Task Force Electronic Trash with questions relating to the discard of e-trash. Most interviewed were male (73%) with aged between 41 and 55 years (40%) and knowledgeable of the event on television. The reason mentioned by the interviewed for participation in the event was the desire to dispose of such materials, especially in their homes. It was observed that in general the prudentinos interviewed had satisfactory level of environmental con